Perencanaan Perawatan dan Perbaikan Genset pada Kereta Api Tipe MTU1600 500 kVA Periode 2024 s.d 2029 - Rosady, Siti Duratun Nasiqiati; Hidayatulloh, Muhammad Kevin Alif (Jurnal INOVATOR, 2025)
Genset or Generator set is a combination device between a power generator (generator) and a driving engine in one set of units to produce electrical power. Genset is a vital device in the modern railway transportation system. In the railway system, electricity generated by the genset is used to supply locomotives, dining cars, passenger cars, power trains, baggage cars, and freight cars. Due to the importance of the genset function in the railway industry, a maintenance and repair planning system is needed to help the continuity of the performance process and the operation of the train run smoothly. To ensure the performance and reliability of the genset, an effective maintenance and repair strategy is needed. One approach that can be used is Failure Mode Effect Analysis (FMEA). The results of genset maintenance and repair using the FMEA method show several critical components, namely the Press Water Pump, Cylinder Head & Gasket, Turbo Charger, Hp Pump, ECU, Injector, Intercooler, Oil Breather, Vibration Damper as well as maintenance and repair schedules (Preventive and Corrective), and the estimated cost required for maintenance and repair in five periods of Rp. 45.131.067,00.